Ifrs 15 adoption, corporate governance and earnings management - Akese-Sarquah Ebenezer (KNUST, 2024)
A thesis submitted to the department of accounting and finance, kwame nkrumah university of science and technology, kumasi in partial fulfilment of the requirement for the award of a degree in master of science accounting and finance